Measuring Gender Equality A Multidisciplinary Analysis of Some EU Countries - di Bella, Enrico; Fachelli, Sandra; López-Roldán, Pedro; Suter, Christian (Social Indicators Research Series, 2023)
In this open access book, the editors explicitly address the issue of measuring gender equality. The book introduces readers to basic concepts of gender equality, equity and equal opportunities, then discusses measuring these phenomena, the methods of constructing indicators, and reviews the main indicators that have been proposed at the international level to measure gender equality. It then sets the theoretical discussions against the findings from a Jean Monnet project financed by the European Union to highlight the importance of a regional analysis of gender equality in four main study areas: Italy, Spain, France and Germany. The results make it clear that it is necessary to move from the purely national perspective hitherto used in gender equality analyses to a regional one because differences can be highly pronounced even within the same country. This is a self-contained volume requiring limited statistical expertise for the reader and is aimed at social researchers and policymakers who wish to address gender equality from a quantitative perspective.